The effect of publication bias magnitude and direction on the certainty in evidence. Issue 3 (12th April 2018) - Murad, Mohammad Hassan; Chu, Haitao; Lin, Lifeng; Wang, Zhen
Abstract : Publication bias occurs when studies with statistically significant results have increased likelihood of being published. Publication bias is commonly associated with inflated treatment effect which lowers the certainty of decision makers about the evidence. In this guide we propose that systematic reviewers and decision makers consider the direction and magnitude of publication bias, as opposed to just the binary determination of the presence of this bias, before lowering their certainty in the evidence. Direction of bias may not always exaggerate the treatment effect. The presence of bias with a trivial magnitude may not affect the decision at hand. Various statistical approaches are available to determine the direction and magnitude of publication bias.